2010
DOI: 10.1002/jbmr.260
|View full text |Cite
|
Sign up to set email alerts
|

Conserved regulatory motifs in osteogenic gene promoters integrate cooperative effects of canonical Wnt and BMP pathways

Abstract: Osteoblast differentiation depends on the coordinated network of evolutionary conserved transcription factors during bone formation and homeostasis. Evidence indicates that bone morphogenetic protein (BMP) and Wnt proteins regulate several steps of skeletal development. Here, we provide a molecular description of the cooperative effects of BMP and Wnt canonical pathway on the expression of the early osteogenic genes Dlx5, Msx2, and Runx2 in C2C12 cells, primary cultures of bone marrow-mesenchymal stem cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 41 publications
(63 reference statements)
3
61
0
Order By: Relevance
“…We next investigated whether canonical BMP Smad signaling was activated in the ARL of the Smad4 mutants. The expression of a well-known BMP downstream target, Msx2, was examined (48,49). Msx2 expression similar to that of controls was detected in the ARL of the Smad4 mutant (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…We next investigated whether canonical BMP Smad signaling was activated in the ARL of the Smad4 mutants. The expression of a well-known BMP downstream target, Msx2, was examined (48,49). Msx2 expression similar to that of controls was detected in the ARL of the Smad4 mutant (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, cycloheximide experiments showed that C4ST-1 is an indirect target of BMP2, BMP7, and TGF␤ signaling (31). In addition, it has been reported that bone formation and homeostasis are propelled by integrated cooperative effects of canonical Wnt and BMP pathways (32) and that C4ST-1 is controlled by BMP pathways during chondrogenesis (20). Therefore, it is suggested that C4ST-1 is regulated in a multistep event by Wnt signaling as well as BMP signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Over 90 mutations of RUNX2 have been reported, including chromosomal translocations, deletions, insertions, nonsense and splice-site mutations, and missense mutation (Zheng et al, 2005), Cunningham et al, (2006), Lo Muzio et al, (2007, Lee et al, (2008) and Ryoo et al, (2010). All of these mutations result in loss of function, leading to only 1 functional copy of the gene and subsequent deficient bone formation in a syndrome known as cleidocranial dysplasia (CCD).…”
Section: Introductionmentioning
confidence: 99%
“…The authors therefore suggested that screening for intragenic deletions and duplications by qPCR or MLPA should be considered for patients with CCD phenotype in whom DNA sequencing does not reveal a causative RUNX2 mutation. Moreover, Ryoo et al, (2010) identified two CCD nuclear families and performed mutational analyses to clarify the underlying molecular genetic etiology. Mutational and phenotypic analyses showed that the severity of mutations on the skeletal system may not necessarily correlate with that of the disruption of tooth development.…”
Section: Introductionmentioning
confidence: 99%